Developing an Automatic 3D Solid Reconstruction System from only Two 2D Views - Hoang, Long; Nguyen, Thanh Tuan; Tran, Hoang Anh; Nguyen, Duc Huy (Engineering, Technology & Applied Science Research, 2024)
Three-dimensional (3D) solid models of mechanical machine parts are widely used in modern mechanical engineering. One expected approach in creating 3D models is automatically reconstructing them from 2D engineering drawings. This work expands the previous automatic reconstruction methods by adding principles, algorithms, and coding to reconstruct oblique planes on the part. The proposed method uses only two views as the input to reconstruct the 3D solid part, including oblique planes. The proposed method has been implemented by a program written in the ARX 2018 language running on the AutoCAD 2021 platform to reconstruct multiple 3D parts from their two views. Experimental test results on many samples confirmed that the proposed method is reliable, absolutely accurate, and achieves a high reconstruction speed. The output 3D model has also been tested and confirmed for compatibility with CAD/CAM software such as Solid Works, Inventor, and PTC Creo.